Understanding COUNTER 5 metrics in context: a case study on vendor database usage reports. Issue 2 (3rd April 2021) - Getsay, Heather; Chen-Gaffey, Aiping
Abstract: This case study examines the COUNTER 5 metrics pertaining to database usage reports, aiming to gain insights into how the metrics function within a vendor platform. By simulating a search process in two major databases, the authors were able to contextualize the numbers in their institution's COUNTER 5 Database Master Reports. The study finds that even though the Release 5 metrics – searches, investigations, and requests – are clearly defined by the COUNTER standard, the vendor platform design has a direct impact on how the usage is actually counted, thus shaping the outcome of a database usage report.